Pengaruh Kemampuan Kerja, Disiplin, Dan Motivasi Terhadap Kinerja Karyawan Pada PT. BPR Lestari Bali - Widiartini, Ni Nyoman Dela; Widhiasthini, Ni Wayan (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study aims to analyze the effect of work ability, discipline and work motivation on employee performance in a company. The research method used is quantitative. The research sample consisted of 61 employees selected by purposive sampling. Data were analyzed using multiple regression tests. The results showed that work discipline has a significant effect on employee performance, with a p-value of 0.025. Meanwhile, work ability and work motivation do not have a significant effect individually on employee performance, with p-values ??of 0.722 and 0.191 respectively. However, work motivation has a significant direct effect on employee performance with a p-value of 0.015, when combined with other variables. Simultaneously, work ability, discipline, and work motivation have a significant effect on employee performance, as evidenced by the F test with a p-value of 0.000.